(untitled) (Plant Tissue Culture and Biotechnology, 2019)
An efficient protocol was standardized for successful regeneration of Cissampelos pareira (L.) through indirect organogenesis. Nodal explants were cultured on MS fortified with 0.5 ± 1.0 mg/l BAP, Kn either single or in combination with NAA 0.5 mg/l. The combinations induced profuse, compact, light green to greenish coloured calli. Some differences in the morphology of callus such as change in the colour and texture was also observed with increasing the concentration of BAP 0.5 ± 2.0 mg/l + NAA 0.5 mg/l. Maximum callus induction was observed on 1.0 mg/l BAP and 0.5 mg/l NAA showed greenish, friable and granular lush colour. The calli were subcultured on fresh MS that contained BAP and Kn single or in combination with NAA (BAP 0.5 ± 2.0 mg/l, Kn 0.5 ± 2.0 mg/l, NAA 0.5 mg/l). The maximum regeneration frequency of shoot organogenesis was recorded on BAP (2.0 mg/l) + NAA (0.5 mg/l). Healthy microshoots were separated and transferred to the rooting medium. Here, MS augmented with IBA 1.0 mg/l showed maximum rooting. Well rooted plantlets were transferred to the field and maximum survival frequency was recorded when BAP (1.0 mg/l) + NAA (0.5 mg/l) for callus induction, for shooting BAP (2.0 mg/l) + NAA (0.5 mg/l) and for rooting IBA (1.0 mg/l) was used. The regenerated whole plants were subjected for hardening where the maximum survival frequency was found to be 80%. This reproducible protocol can be used for regeneration and genetic transformation studies.